Local embeddedness, upgrading and skill development : global value chains and foreign direct investment in Lesotho’s apparel industry /: global value chains and foreign direct investment in Lesotho’s apparel industry. (February 2013) - Staritz, Cornelia; Morris, Mike, 1949-
No abstract available